Extractive desulfurization of model fuel oil using ester functionalized imidazolium ionic liquids - Raj, J.J. (Elsevier B.V., 2018)
A series of ester functionalized imidazolium ionic liquids (ILs) with varying alkyl chain length were synthesized and characterized. Dicyanamide was chosen as the anion for these series of ILs. NMR (1H and 13C) and elemental analysis were used to confirm the structure of ILs. Thermal analysis (TGA) revealed that the synthesized ILs have good thermal stability up to 180 Â°C. The ILs were screened by COSMO-RS to further investigate their Ï surface, Ï potential and Ï profile to obtain better understanding on the nature of interaction of ILs with sulfur compounds. The effect of temperature, time and mass ratio (ILs: model oil) were studied for the extraction of dibenzothiophene (DBT) from model oil using the synthesized ILs. The extractive desulfurization of model oil containing DBT in n-dodecane revealed that the ester functionalized ILs with an alkyl length of six carbon atoms, C2COOCH3ImC6H13N(CN)2 is the most promising candidate. More than 80% of DBT was extracted in 15 min with a mass ratio (ILs: model oil) of 2:1 at 25 Â°C. This high efficiency was observed in a single stage extraction, which indicated that the ester based ILs are an ideal candidate for the removal of DBT in a short extraction period. The ILs had good reusability up to 10 cycles with high extraction efficiency. The toxicity profile of ILs were assessed to evaluate their impact on environment and living organisms. Microbial toxicity studies depicted that the ILs can be considered as âpractically harmlessâ. Â© 2017 Elsevier B.V.